2019
DOI: 10.18552/2019/idscmt5176
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of industrial by-products as sustainable practice against the exploitation of virgin materials

Abstract: The rise in population and competitiveness among growing economies to stamp their superiority are some of the prime reasons for natural materials to disappear rapidly. This research involves the utilization of industrial by-products, namely rice husk ash (RHA), fly ash (FA), palm oil fuel ash (POFA), palm oil clinker powder (POCP), oil palm shell (OPS), and palm oil clinker (POC) as alternatives in the development of both conventional and geopolymer concretes; notably, OPS was used as whole replacement for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…McLellan et al [95] observed similar research result that geo-polymer like POFA and POCP technology in concrete would minimize 44-64% of CO2-e [94]. By using these industrial by-products in concrete, more than 50 percent of CO2-e can be reduced [37]. Table 6 indicates that the CO2-e emission of palm oil residue material compared to conventional OPC is much lower.…”
Section: Reduction Of Carbon Footprintmentioning
confidence: 74%
“…McLellan et al [95] observed similar research result that geo-polymer like POFA and POCP technology in concrete would minimize 44-64% of CO2-e [94]. By using these industrial by-products in concrete, more than 50 percent of CO2-e can be reduced [37]. Table 6 indicates that the CO2-e emission of palm oil residue material compared to conventional OPC is much lower.…”
Section: Reduction Of Carbon Footprintmentioning
confidence: 74%